2020
DOI: 10.1080/23802359.2020.1717385
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of a yellow-bellied sea snake (Hydrophis platurus) (Squamata, Elapidae)

Abstract: In this study, we provide the first report of the complete mitochondrial genomic sequencing of a yellow-bellied sea snake (Hydrophis platurus) that has the broadest distribution range of all Squamata species. The mitogenome length was 18,101 bp and consisted of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 3 non-coding regions. The sequence presented could be very useful for further phylogenetic and evolutionary studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…During the course of the present study, complete mtDNA sequences were reported for three semiaquatic sea snakes of the genus Laticauda and several fully aquatic sea snakes of the genera Emydocephalus and Hydrophis (all in the subfamily Hydrophiinae) [ 40 , 41 , 42 , 43 , 44 , 45 ]. Among them, E. ijimae (Accession No.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the present study, complete mtDNA sequences were reported for three semiaquatic sea snakes of the genus Laticauda and several fully aquatic sea snakes of the genera Emydocephalus and Hydrophis (all in the subfamily Hydrophiinae) [ 40 , 41 , 42 , 43 , 44 , 45 ]. Among them, E. ijimae (Accession No.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophis melanocephalus, a rarely studied slender-necked sea snake, has been often confused with other snakes, such as H. coggeri in the Australian region (Kharin 1984), Emydocephalus ijimae in Japan (Yi et al 2019), and H. platurus and Laticauda semifasciata in Korea (Kim et al 2018;Kim et al 2020). Hydrophis melanocephalus is known to be distributed in Vietnam, China, Taiwan, Japan, and Philippines (David and Ineich 1999;Kharin and Czeblukov 2006).…”
mentioning
confidence: 99%